PENGARUH BALIKAN (FEEDBACK) GURU DALAM PEMBELAJARAN TERHADAP MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK (SUATU KAJIAN TEORITIS DAN EMPIRIK) - Sumarno Sumarno (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2016)
Feedback in learning is defined as information that is communicated to students that aims to change the thinking or behavior to improve the learning process. Giving feedback by teachers in teaching is an important activity to improve their knowledge and acquisition capabilities, accomplishments, and motivate learners. The researchers recommend the characteristics of effective feedback in learning must be non-evaluative, supportive, timely, and specific. Feedback provided in the form of learning on the learner information in response to action learning activities that have been carried out. Feedback can be presented in various forms, for example in the form of verification of the accuracy of the answers, an explanation of the correct answer, instructions and examples as well as performed at any time during the learning process, such as it provides answers, or after a certain time lag. Effect of feedback in learning can be explained with reference to the learning theories, namely the theory of behaviorism, cognitivism, constructivism and learn some vital lessons theory of self-regulation.